2015
DOI: 10.1134/s1063785015050296
|View full text |Cite
|
Sign up to set email alerts
|

Model calculation of the charge composition of a plasma in a vacuum-arc discharge with a composite cathode

Abstract: Composite cathodes manufactured by mixing (sin tering or melting) various components in the desired proportion are widely used to obtain various func tional coatings by electric arc spraying. In particular, titanium-aluminum composite cathodes are used to deposit wear resistant and heat resistant coatings on cutting tools [1]. During spraying of a composite cath ode in a vacuum arc source material for multicompo nent ion deposition (implantation), the main task is to form a near surface layer with a certain st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…In a number of studies (see, e.g. [5,6,[14][15][16][17][18]), it was shown that simulation models based on the equations of magnetohydrodynamics are quite applicable to describe the evolution of the cathode jet plasma in vacuum arcs with pure metal cathodes and give predictions consistent with the experimental data. In particular, it was shown that the plasma expansion near a cathode spot cell is almost spherically symmetric [14].…”
Section: Mhd Model Of the Plasma Jet Generated By A Cell Of The Catho...mentioning
confidence: 98%
“…In a number of studies (see, e.g. [5,6,[14][15][16][17][18]), it was shown that simulation models based on the equations of magnetohydrodynamics are quite applicable to describe the evolution of the cathode jet plasma in vacuum arcs with pure metal cathodes and give predictions consistent with the experimental data. In particular, it was shown that the plasma expansion near a cathode spot cell is almost spherically symmetric [14].…”
Section: Mhd Model Of the Plasma Jet Generated By A Cell Of The Catho...mentioning
confidence: 98%
“…In this case the ions of different mass will have the same average velocity due to very strong ion-ion collision in dense cathode spot plasma [10]. In the framework of the model of [11] the calculated average velocity of Zn-Pb plasma was 0.61*10 6 cm/s for all ion types. It is necessary to clarify that the ions originated from the cathode spots have quite a wide distribution of kinetic energy [12].…”
Section: Resultsmentioning
confidence: 92%
“…At different stages of the cycle the ions emitted from the spot have different drift velocities, but at any stage the ions with different charges have the same drift velocity [14]. From this viewpoint the velocity obtained within the model of [11] can be treated as a velocity averaged over the ecton cycle [1,13]. The ion flux angular distributions calculated for this case are shown in Figure 8.…”
Section: Resultsmentioning
confidence: 99%